Composite solid-state polymer electrolyte cspe separator and preparation method and application thereof
Patent Information
- Application Number
- CN202310880051.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-18
AI Technical Summary
传统的固态聚合物电解质(SPEs)是在聚环氧乙烷(PEO)基底中添加一定比例的小分子锂盐(LITFSI),虽然当小分子锂盐的比例增大到一定程度时,可以获得较高的离子电导率,但这是以牺牲隔膜的机械性能为代价
[0049](1)本发明将LiPEBI单离子导电聚合物电解质应用于PEO/LiTFSI体系中,得到复合固态聚合物电解质。聚合物LiPEBI不仅具有超离域性质的双磺酰亚锂载流子,有助于进一步降低PEO的结晶度,聚阴离子(-SO2N-SO2-)和柔性的烷氧链还可以为锂离子的传导提供离子通道。此外,单离子聚合物电解质的添加,对于提高锂离子迁移数,缓解电池运行过程中产生的浓差极化也具有重要意义。
Smart Images

Figure CN116742276B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium metal battery technology, specifically relating to a composite solid polymer electrolyte (CSPE) separator, its preparation method, and its application. Background Technology
[0002] All-solid-state lithium metal batteries (ASSLMBs) are considered highly promising for future energy storage due to their high energy density, high rated voltage, good safety performance, and light weight. Traditional solid-state polymer electrolytes (SPEs) consist of a polyethylene oxide (PEO) substrate with a certain proportion of small-molecule lithium salts (LITFSI). While increasing the proportion of small-molecule lithium salts to a certain extent can achieve high ionic conductivity, this comes at the cost of sacrificing the mechanical properties of the separator. Furthermore, small-molecule lithium salts are prone to concentration polarization during battery operation, leading to the depletion of anions on the negative electrode surface and the formation of an "ion depletion layer." This is the main cause of dendrite formation on the lithium metal surface. Excessive growth of lithium dendrites can puncture the separator, causing a short circuit and potentially leading to spontaneous combustion, explosion, and other safety accidents.
[0003] Numerous studies have confirmed the significant role of single-ion polymers in suppressing lithium dendrite growth, which is of great reference value for improving the safety performance of all-solid-state lithium metal batteries. Yang et al. successfully prepared lithium-ionized polydopamine-modified graphene oxide nanosheets (LiDGO) and added them to the PEO and LITFSI system, significantly improving the mechanical and electrochemical properties of SPEs. The ionic conductivity at 30℃ reached 3.4 × 10⁻⁶. -5 S cm -1 It exhibits a high discharge specific capacity (156 mAh g) during battery cycling. -1 It exhibits high capacity retention (98.7%) and stable coulombic efficiency, and demonstrates low polarization voltage during lithium battery operation. SEM image analysis shows that the addition of LiDGO effectively suppresses lithium dendrite growth, which is significant for improving battery safety performance.
[0004] Based on the above reasons, this application is hereby submitted. Summary of the Invention
[0005] In this application, the inventors applied the LiPEBI single-ion conductive polymer electrolyte to a PEO / LiTFSI system to obtain a composite solid polymer electrolyte. The polymer LiPEBI not only possesses hyperlocalized lithium bissulfonylidene charge carriers, which helps to further reduce the crystallinity of PEO, but also... -SO2- and flexible alkoxy chains can also provide ion channels for lithium-ion conduction. Furthermore, the addition of single-ion polymer electrolytes is significant for increasing lithium-ion transport numbers and mitigating concentration polarization during battery operation.
[0006] Based on the above reasons, and in view of the problems or defects existing in the prior art, the purpose of this invention is to provide a composite solid polymer electrolyte (CSPE) membrane, its preparation method and application, to solve or at least partially solve the above-mentioned technical defects existing in the prior art.
[0007] To achieve the first objective of this invention, the technical solution adopted by this invention is as follows:
[0008] A method for preparing a composite solid polymer electrolyte (CSPE) membrane includes the following steps:
[0009] Polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and single-ion polymer electrolyte LiPEBI were weighed according to the specified ratio, mixed, and dissolved in deionized water. The resulting mixed solution was then heated to 50–70°C and stirred for 10–15 hours. The resulting solution was then uniformly coated onto the substrate surface, dried, and finally removed from the substrate to obtain the composite solid polymer electrolyte CSPEs membrane.
[0010] Furthermore, in the above technical solution, the EO in PEO and the Li in LiTFSI + The molar ratio is 45:1.
[0011] Furthermore, in the above technical solution, the amount of the single-ion polymer electrolyte LiPEBI added is 10% of the total mass of PEO and LiTFSI.
[0012] Furthermore, in the above technical solution, the amount of deionized water added is not specifically limited, as long as the uniform dissolution of the above three substances (PEO, LiTFSI and LiPEBI) can be achieved.
[0013] Furthermore, in the above technical solution, the substrate is preferably a glass plate or the like.
[0014] Furthermore, in the above technical solution, the drying temperature is 40–60°C, and the drying time is 12–24 hours. In a preferred embodiment of the present invention, the drying temperature is 50°C, and the drying time is 18 hours.
[0015] Furthermore, in the above technical solution, the single-ion polymer electrolyte LiPEBI is prepared by the following method, including the following steps:
[0016] Weigh an appropriate amount of di(bis(sulfonylimide)benzenediacarboxylic acid) precursor (OX-BCSI) and place it in a double-necked flask 1 equipped with a water separator. Then, add anhydrous lithium chloride according to the ratio, purify the mixture with cooling water, and then introduce pure argon gas into the double-necked flask 1 to protect the reaction. Next, add anhydrous nitrogen-methylpyrrolidone (NMP), pyridine (Py), and triphenyl phosphite (TPP) to the double-necked flask 1 according to the ratio. After stirring and dissolving at room temperature, add 1,2-bis(2-aminoethoxy)ethane to the reaction system. Then, heat the system to 80-120°C and react at a constant temperature for 20-30 hours. After the reaction is completed, cool to room temperature, precipitate the yellow solid in the resulting reaction solution, filter, wash the filter cake, and obtain the yellow product. Finally, dry the yellow product, lithiumize it, filter it after complete lithiumization, wash the filter cake, and dry it to obtain the target product, the single-ion polymer electrolyte LiPEBI.
[0017] Furthermore, in the above technical solution, the molar ratio of the di(bis(sulfonylimide)benzenediacarboxylic acid precursor to anhydrous lithium chloride is 1:4.
[0018] Furthermore, in the above technical solution, the ratio of the di(bis(sulfonylimide)benzenediacarboxylic acid precursor to anhydrous nitrogen methylpyrrolidone is (3-4) parts by mass : (20-50) parts by volume, wherein the parts by mass and parts by volume are based on g:mL.
[0019] Furthermore, in the above technical solution, the ratio of the di(bis(sulfonylimide)benzenediacarboxylic acid precursor to pyridine is (3-4) parts by mass: (10-20) parts by volume, wherein the parts by mass and parts by volume are based on g:mL.
[0020] Furthermore, in the above technical solution, the ratio of the di(bis(sulfonylimide)benzenediacarboxylic acid precursor to triphenyl phosphite is (3-4) parts by mass : (3-10) parts by volume, wherein the parts by mass and parts by volume are based on g:mL.
[0021] Furthermore, in the above technical solution, the molar ratio of the di(bis(sulfonylimide)benzenediacarboxylic acid precursor to 1,2-bis(2-aminoethoxy)ethane is 1:1.
[0022] Furthermore, in the above technical solution, the reaction temperature is preferably 100℃ and the reaction time is preferably 24h.
[0023] Furthermore, in the above technical solution, the preferred method for the precipitation of the yellow solid is as follows: the obtained reaction solution is slowly poured into an excess of anhydrous methanol, and the methanol solution is stirred with a glass rod while pouring until the yellow solid is completely precipitated.
[0024] Furthermore, in the above technical solution, the drying process is specifically as follows: baking at 80-100℃ for 30-40 hours. In a preferred embodiment of the present invention, the drying is carried out in two stages: first, baking in a forced-air drying oven at 80-120℃ for 2-5 hours to remove most of the solvent, and then transferring to a vacuum drying oven at 80-120℃ for 2-5 hours to remove the remaining trace amounts of residual solvent.
[0025] Furthermore, in the above technical solution, the specific lithiation process is as follows: the yellow product is dispersed in a methanol solution of lithium hydroxide according to the specified ratio, and the mixture is stirred and reacted at room temperature under an inert atmosphere for 18–30 hours. In a preferred embodiment of the present invention, to ensure sufficient lithiation, the lithiation is performed in two stages, each lasting 12 hours.
[0026] Preferably, in the above technical solution, the concentration of the lithium hydroxide methanol solution is 0.05–0.15 mol / L.
[0027] Furthermore, in the above technical solution, the di(bis(sulfonylimide)benzenediacarboxylic acid precursor is prepared by the following method, with the following steps:
[0028] (1) Weigh p-toluenesulfonyl and potassium hydroxide into a reaction flask according to the ratio, then add deionized water and stir until completely dissolved; adjust the temperature of the resulting solution to 75-85℃, then weigh 4,4'-oxobis(benzenesulfonyl chloride) according to the ratio and slowly add it into the reaction flask in batches; after the addition is complete, adjust the reaction temperature to 90-100℃ and react at a constant temperature for 10-15 hours.
[0029] After the reaction was completed, dilute hydrochloric acid solution was added to the product while it was still hot to adjust the pH of the product to 7; then the product was filtered, the filtrate was collected, and dilute hydrochloric acid solution was added to the filtrate to adjust the pH of the filtrate to 1, resulting in a milky white precipitate. The white precipitate was collected by centrifugation and recrystallized to obtain the di(bis(sulfonylimide)phenyldimethyl precursor OX-BMSI).
[0030] (2) Synthesis of OX-BCSI
[0031] Weigh the OX-BMSI and potassium hydroxide from step (1) according to the specified ratio, and add them sequentially to a double-necked flask 2 equipped with a water separator. Then add deionized water and, after complete dissolution, heat the system to 85-95°C and introduce cooling water. Subsequently, slowly add potassium permanganate to the double-necked flask 2 at 85-95°C. After the addition is complete, stir the reaction at a constant temperature for 10-15 hours. After the reaction is complete, cool to room temperature, filter the obtained product, add excess concentrated hydrochloric acid to the filtrate, let it stand, filter again to obtain the crude product, recrystallize, and dry to obtain the di(bis(sulfonylimide)benzenediacarboxylic acid precursor OX-BCSI.
[0032] Preferably, in step (1) of the above technical solution, the molar ratio of p-toluenesulfonamide to potassium hydroxide is 1:1.
[0033] Preferably, in step (1) of the above technical solution, the molar ratio of p-toluenesulfonamide to 4,4'-oxobis(benzenesulfonyl chloride) is 4:1.
[0034] Preferably, in step (1) of the above technical solution, the amount of deionized water is not specifically limited, as long as it can achieve uniform dissolution of p-toluenesulfonamide and potassium hydroxide. In a preferred embodiment of the present invention, the ratio of p-toluenesulfonamide to deionized water is 0.048 mol: 15 mL.
[0035] Preferably, in step (1) of the above technical solution, the reaction temperature is 95°C and the reaction time is 12h.
[0036] Preferably, in step (2) of the above technical solution, the molar ratio of OX-BMSI to potassium hydroxide is 1:2.
[0037] Preferably, in step (2) of the above technical solution, the amount of deionized water is not specifically limited, as long as it can achieve uniform dissolution of OX-BMSI and potassium hydroxide. In a preferred embodiment of the present invention, the ratio of OX-BMSI to deionized water is 0.006 mol: 200 mL.
[0038] Preferably, in step (2) of the above technical solution, the molar ratio of OX-BMSI to potassium permanganate is 2:1.
[0039] Preferably, in step (2) of the above technical solution, the potassium permanganate is added at a time not exceeding 2 hours.
[0040] Preferably, in step (2) of the above technical solution, the settling time is 20-40 minutes.
[0041] A second objective of this invention is to provide a composite solid polymer electrolyte membrane prepared by the method described above.
[0042] A third objective of this invention is to provide the application of the composite solid polymer electrolyte separator prepared by the above-described method in lithium metal batteries.
[0043] A lithium metal battery includes a positive electrode, a negative electrode, a solid electrolyte membrane, an electrolyte, and a shell, wherein the solid electrolyte membrane is the composite solid polymer electrolyte membrane described above in this invention.
[0044] Furthermore, in the above technical solution, the positive electrode sheet includes a positive electrode active material, a conductive material, and a binder. The positive electrode active material is lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), or lithium nickel cobalt manganese oxide (LiNi). x Co y Mn z Any one of O2 and lithium manganese oxide (LiMn2O4).
[0045] Preferably, in the above technical solution, the preparation method of the positive electrode sheet includes the following steps: mixing the positive electrode active material, conductive material, and binder in a mass ratio of 7:2:1, using N,N-2-methylpyrrolidone as a solvent, thoroughly grinding to form a slurry, then coating it onto aluminum foil using a wet film preparation device, and vacuum drying at 80°C for 12 hours. After drying, using a cutting tool, cutting the aluminum foil coated with the sample into ready-made electrode sheets.
[0046] Furthermore, in the above technical solution, the negative electrode is a lithium metal disc.
[0047] Furthermore, in the above technical solution, the electrolyte is a 1M LiPF6 EC / DMC (1:1, v / v) solution or a pure EC / DMC (1:1, v / v) solution.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] (1) This invention applies the LiPEBI single-ion conductive polymer electrolyte to the PEO / LiTFSI system to obtain a composite solid polymer electrolyte. The polymer LiPEBI not only possesses hyperlocalized lithium bissulfonylidene charge carriers, which helps to further reduce the crystallinity of PEO, but also... - SO2- and flexible alkoxy chains can also provide ion channels for lithium-ion conduction. Furthermore, the addition of single-ion polymer electrolytes is significant for increasing lithium-ion transport numbers and mitigating concentration polarization during battery operation.
[0050] (2) In the PEO / LiTFSI electrolyte system, the lithium-ion transference number is only 0.15 due to the inherent mobility of anions. However, after adding 10% by mass of the single-ion polymer LiPEBI, the lithium-ion transference number reaches 0.44, an increase of nearly three times. Furthermore, at a current density of 0.05 mA / cm², the lithium-ion transference number also increases. -2 When using a composite solid polymer electrolyte membrane, the system exhibits superior peeling / deposition stability and can cycle stably for 500 hours, outperforming the PEO / LiTFSI electrolyte system's 240 hours.
[0051] (3) The ionic conductivity at room temperature and 60°C was 7.69 × 10⁻⁶ when the addition amount was 10%. -6 S cm -1 and 4.16×10 -4 S cm -1 All of these values are higher than the 2.83 × 10⁻⁶ of the PEO / LiTFSI electrolyte system. -6 S cm -1 and 2.40×10 -4 S cm -1 Furthermore, the battery assembled using this system exhibited an initial discharge specific capacity of 137.3 mAh g⁻¹ at 60°C and a current density of 0.4C. -1 After 100 charge-discharge cycles, it still has 128.8 mAh g. -1 The capacity decreased by only 6.2% of the initial capacity, and the coulomb efficiency remained at around 98%. Attached Figure Description
[0052] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0053] Figure 1 This is a schematic diagram of the composite solid polymer electrolytes (CSPEs) of the present invention;
[0054] Figure 2 (a) SEM images of the composite solid polymer electrolyte membrane prepared in Example 1: planar × 500; cross-section × 500; (c) EDS mapping of N element; (d) Tyndall effect of the prepared homogeneous solution; (eg) physical bending properties of the composite solid polymer electrolyte membrane;
[0055] Figure 3 The composite solid polymer electrolyte membrane prepared in Example 1: (a) DSC curve; (b) TG curve;
[0056] Figure 4 (a) Time-current curves of the insertion impedance plot: (b) PEO / LiTFSI electrolyte membrane prepared in Comparative Example 1; (c) Long-term constant current cycling test of lithium symmetric battery;
[0057] Figure 5Surface morphology of lithium sheet: (ab) Optical image of the original lithium sheet, SEM plane; (cd) Optical image of the lithium sheet after 240h constant current cycling with PEO / LiTFSI electrolyte prepared in Comparative Example 1, SEM plane; (ef) Optical image of the lithium sheet after 500h constant current cycling with composite solid polymer electrolyte membrane, SEM plane.
[0058] Figure 6 (a) LSV at 60°C; (b) Interfacial resistance at 60°C; (c) Ionic conductivity; (d) Rate performance of LiFePO4|Li battery at 60°C; (ef) Charge-discharge curves; (g) Cycling performance of LiFePO4|Li battery at 0.4C at 60°C. Detailed Implementation
[0059] The present invention will be further described in detail below through implementation examples. These implementation examples are carried out based on the technology of the present invention. Detailed implementation methods and specific operating procedures are provided to illustrate the inventiveness of the present invention, but the scope of protection of the present invention is not limited to the following implementation examples.
[0060] Based on the information contained in this application, various modifications to the precise description of the invention can be readily made by those skilled in the art. It should be understood that the scope of the invention is not limited to the defined processes, properties, or components, as these embodiments and other descriptions are merely illustrative of specific aspects of the invention.
[0061] To better understand the invention and not to limit its scope, all figures indicating amounts, percentages, and other numerical values used in this application should, in all cases, be understood to be modified by the word "approximately." Therefore, unless otherwise stated, the numerical parameters listed in the specification are approximate values and may vary depending on the desired properties being sought. Each numerical parameter should at least be considered as obtained based on reported significant figures and through conventional rounding methods.
[0062] The equipment and raw materials used in this invention are all commercially available or commonly used in the field. Unless otherwise specified, the methods in the following embodiments are conventional methods in the field.
[0063] Example 1
[0064] The preparation method of a composite solid polymer electrolyte (CSPE) membrane according to this embodiment includes the following steps:
[0065] With EO:Li +A certain mass of PEO and LiTFSI were weighed out in a 45:1 ratio, and 10% of the total mass of the single-ion polymer electrolyte LiPEBI was weighed out. A certain proportion of deionized water was added to dissolve all three components, and the mixture was heated and stirred at 60°C for 12 hours. The prepared solution was then evenly coated onto a glass plate, which was placed on a 50°C heating plate for 18 hours to allow complete evaporation of the water. Finally, the composite solid polymer electrolyte membrane was removed from the glass plate and placed in a 50°C vacuum oven to dry for later use.
[0066] The single-ion polymer electrolyte LiPEBI described above is prepared by the following method:
[0067] (1) Synthesis of the bis(bissulfonylimide)phenyldimethyl precursor:
[0068] Weigh 8.22 g (0.048 mol) of p-toluenesulfonamide and 2.69 g (0.048 mol) of potassium hydroxide granules into a 25 mL double-necked flask, add 15 mL of deionized water, and stir until completely dissolved. Adjust the solution temperature to 80 °C. Weigh 4.41 g (0.012 mol) of 4,4'-oxobis(benzenesulfonyl chloride) and slowly add it in batches to the reaction flask using a spatula. After the addition is complete, adjust the reaction temperature to 95 °C and allow it to react completely for 12 h.
[0069] After the reaction was complete, the solution was transferred to a 50 mL beaker while still hot. 0.1 mol / L hydrochloric acid solution was added to adjust the pH of the reaction solution to 7, resulting in a white precipitate. The filtrate was collected after filtration, and hydrochloric acid solution was added again to adjust the pH to 1, yielding a milky white precipitate. The white precipitate was collected by centrifugation and recrystallized to obtain the product, di(bis(sulfonylimide)phenyldimethyl) precursor. After drying, the product weighed 6.624 g, with a yield of 86.7%.
[0070] (2) Synthesis of the bis(bissulfonylimide)benzenedicarboxylic acid precursor
[0071] 3.816 g (0.006 mol) of dried OX-BMSI precursor and 0.672 g (0.012 mol) of potassium hydroxide were weighed and added sequentially to a 500 mL double-necked flask equipped with a Dean-Stark separator. 200 mL of deionized water was added to completely dissolve the precursor, and cooling water was introduced. Then, 4.74 g (0.03 mol) of potassium permanganate was weighed and slowly added to the solution at 90 °C (over 2 h). The solution turned purple-red at this point. The reaction was stirred for 12 h. After the reaction was complete, heating was stopped and the solution was allowed to cool to room temperature. The solution was filtered to obtain a colorless, transparent solution. Excess concentrated hydrochloric acid was added dropwise to the filtrate, resulting in the precipitation of a large amount of white precipitate. After standing for 30 min, the crude product was obtained by filtration. Finally, the crude product was recrystallized in deionized water and dried to obtain 3.587 g of the target product, di(bis(sulfonylimide)benzenediacarboxylic acid) precursor, with a yield of 85.8%.
[0072] (3) Synthesis of ionic polymer electrolyte LiPEBI
[0073] Weigh 3.6 g (5.2 mmol) of bis(bissulfimide)benzenediacarboxylic acid precursor and place it in a 100 mL double-necked flask equipped with a Dean-Stark water separator. Then add 0.88 g (20.8 mmol) of anhydrous lithium chloride. Set up the apparatus and purge with cooling water to fill the apparatus with pure argon gas. Using a disposable syringe, add 30 mL of NMP, 15 mL of Py, and 5.2 mL of TPP sequentially through rubber stoppers to the double-necked flask. After dissolving by stirring at room temperature, inject 0.77 g (5.2 mmol) of 1,2-bis(2-aminoethoxy)ethane into the reaction flask. Then heat to 100 °C and react for 24 h. After the reaction is complete, cool to room temperature and slowly pour the reaction solution into excess anhydrous methanol. While pouring, stir the methanol solution with a glass rod until a yellow solid completely precipitates. Filter, remove the filtrate, and wash the filter cake repeatedly with methanol three times to obtain the yellow product. The product was dried in an 80℃ forced-air oven for 10 hours, and then dried in a 100℃ vacuum oven for 24 hours. After removing the sample, it was lithiated twice with 0.249 g (10.4 mmol) of anhydrous LiOH in 100 mL of methanol solution, 12 hours each time, to ensure complete lithiation. After complete lithiation, the sample was filtered, and the filter cake was washed twice with anhydrous methanol and dried to obtain the target product, the ionic polymer electrolyte LiPEBI.
[0074] Comparative Example 1
[0075] The preparation method of the PEO / LiTFSI blank membrane in this comparative example is basically the same as that in Example 1, except that the raw material single-ion polymer electrolyte LiPEBI was not used in this comparative example, and all other conditions are the same.
[0076] Physical property testing of composite solid polymer electrolyte membrane
[0077] from Figure 2 The SEM images of the ab composite solid polymer electrolyte membrane show that the single-ion polymer electrolyte LiPEBI is uniformly distributed in the PEO matrix without significant agglomeration. This is beneficial for regulating the uniform deposition of lithium ions. The thickness of the composite solid polymer electrolyte membrane is about 119 μm. Figure 2 c is the X-ray energy dispersive spectroscopy image of nitrogen in the composite solid polymer electrolyte membrane, which further proves the good dispersibility of polymer lithium salt LiPEBI and small molecule lithium salt LiTFSI in the matrix. Figure 2 d represents the solution used to prepare the composite solid polymer electrolyte membrane. Irradiating the solution with a red laser reveals a bright pathway, demonstrating the good solubility and compatibility of the lithium salt and PEO matrix in the solvent. The composite solid polymer electrolyte membrane completely recovers its original shape after being bent and folded, exhibiting good mechanical properties, such as… Figure 2 As shown in the example.
[0078] In all-solid-state polymer electrolytes, lithium-ion conduction relies entirely on the polar groups on the polymer chains that can complex with lithium ions, as well as the state of the polymer chain segments themselves. According to the "amorphous region diffusion conduction model theory," the amorphous state of a material favors chain segment movement, and lithium ions move along with the flexible polymer chain segments. Therefore, reducing the crystallinity of PEO is crucial for improving the performance of all-solid-state batteries, often requiring the polymer to have a low glass transition temperature (Tg). In this invention, the inventors used differential scanning calorimetry (DSC) to investigate the glass transition temperature, melting point (Tm), and crystallinity of the polymer.
[0079] The thermal stability of the composite solid polymer electrolyte was tested using a thermogravimetric analyzer (TGA), and the data were directly read from the mass decay curve. The results are as follows: Figure 3 As shown in figure a, PEO exhibits a distinct melting transition peak at 67.78℃, which is consistent with previous reports on PEO. It is noteworthy that the Telectrolyte of the composite solid polymer electrolyte membrane... g and T m The temperature drop is 1.66℃ and 0.96℃ lower than that of the PEO / LiTFSI electrolyte membrane, respectively. This may be because LiPEBI disrupts the ordered structure of the PEO chain segments, increases the proportion of the amorphous phase region, and under the influence of electrostatic attraction, Li... + The Li-ion moves back and forth from the PEO segments to the polyanion. Similar to the phenomenon observed in other PEO / SIPEs systems, dissolved Li-ion in PEO... +Increased concentration leads to decreased crystallinity. Using the formula relating enthalpy of fusion to crystallinity, the CSPEs((ΔH)) can be calculated. m =72.79J g -1 ) and PEO / LiTFSI(ΔH m =90.41J g -1 The crystallinity of PEO in the electrolytes was 47.2% and 52.7%, respectively, consistent with the above analysis. Therefore, compared with the PEO / LiTFSI electrolyte, the PEO in the composite solid polymer electrolyte has a higher degree of amorphous phase and segmental motion, which is beneficial to improving its ionic conductivity. Thermogravimetric analysis (TG) is often used to characterize the thermal stability of substances, such as... Figure 3 As shown in b, the thermal decomposition temperatures of PEO and the PEO / LiTFSI system are both close to 400℃, exhibiting good high-temperature resistance. Among them, the composite solid polymer electrolyte membrane has the highest mass retention after thermal decomposition, which is due to the unique benzene ring structure in the single-ion polymer electrolyte LiPEBI.
[0080] The testing process for lithium-ion transference number (LTN) and lithium stripping / deposition stability of composite solid polymer electrolytes is as follows: The lithium-ion transference number (LTN) test method is as follows: The LTN reflects the migration of cations and anions during battery operation. This experiment was conducted on a VMP3 electrochemical workstation, testing a symmetric Li|film|Li battery. The LTN in the polymer electrolyte of the lithium battery cell was calculated using the steady-state current method. This value was calculated using the following formula:
[0081]
[0082] Where I0 and I s These are the initial current and steady-state current, respectively. ΔV is the set polarization voltage, and R0 and R... s These represent the initial resistance and steady-state resistance of the lithium electrode passivation layer. Lithium stripping-deposition stability testing was conducted on a LAND testing system, using an assembled Li|film|Li battery at a current density of 2.5 mA cm⁻¹. -2 / 0.05mA cm -2 The peeling and electroplating times were both 1 hour.
[0083] Table 1. Lithium-ion transference number test results
[0084]
[0085] The transport number of lithium ions in different electrolyte systems was tested using the steady-state current method at 60℃. The impedance spectra of DC polarization and the response over time are shown below. Figure 4As shown in ab, detailed results are summarized in Table 1. In the PEO / LiTFSI electrolyte system, the lithium-ion transference number is only 0.15 due to the inherent mobility of anions. However, after adding 10% by mass of the single-ion polymer LiPEBI, the lithium-ion transference number reaches 0.44, an increase of nearly three times. This is due to the disulfonamide (-SO2N) - SO2-) anions are anchored on the polymer chain, and the increase in lithium-ion transference number will help alleviate concentration polarization during battery operation, which is of practical significance for suppressing lithium dendrite growth and extending battery life.
[0086] The stripping / deposition stability of the two electrolyte systems was tested by long-term constant current cycling through a lithium symmetric battery at 60°C. Figure 4 As shown in Figure c, when the current density is 0.05 mA cm⁻¹ -2 At that time, the system using composite solid polymer electrolyte membranes (CSPEs) exhibited superior peeling / deposition stability, achieving stable cycling for 500 hours, which is superior to the 240 hours of the PEO / LiTFSI electrolyte system. Figure 4 The embedding plot of c provides a clearer and more intuitive observation that, during 85-88 hours, compared to the high polarization potential of 185 mV exhibited by the PEO / LiTFSI electrolyte system, the system using composite solid polymer electrolyte membranes (CSPEs) displayed a very stable and lower polarization potential of 54 mV. This is not only due to t Li + The significant improvement effectively reduced the concentration polarization of ions inside the battery, which can also be attributed to the good compatibility between the polar groups in the LiPEBI molecular structure and the electrode interface.
[0087] The surface morphology of lithium metal in a lithium symmetric battery after constant current cycling was examined to verify the inhibitory effect of the single-ion polymer electrolyte LiPEBI on lithium dendrite growth during long-term electroplating / stripping. Figure 5 ab presented optical photographs and SEM images of the original lithium wafer, both showing a smooth and flat surface morphology. However, as... Figure 5 As shown in Figure 1, the lithium sheet surface of the PEO / LiTFSI electrolyte system prepared in Comparative Example 1 was very rough after 240 hours of constant current cycling, with obvious dead lithium accumulation. The SEM images clearly show a large number of dendrites growing on the lithium sheet surface. In contrast, the composite solid polymer electrolyte (CSPE) membrane system prepared in Example 1, after a longer cycling time (500 hours), showed significantly less dead lithium accumulation, and the lithium sheet still retained a certain metallic luster, as seen in both optical and SEM images. Figure 5These results indicate that a uniform distribution of lithium ions in composite solid polymer electrolyte membranes (CSPEs) is beneficial for achieving uniform Li-ion exchange. + Stripping / coating can effectively suppress the growth of lithium dendrites. This is also due to the fact that the single-ion polymer electrolyte LiPEBI increases the lithium-ion transference number of the composite solid polymer electrolyte membrane.
[0088] The electrochemical performance and battery performance testing process of the composite solid polymer electrolyte (CSPE) membrane are as follows: Linear sweep voltammetry (LSV) was used to measure the electrochemical stability window of the composite polymer electrolyte, providing a direct measurement of its electrochemical stability. LSV is commonly used to study the electrochemical performance of batteries. A triangular wave voltage is used to scan between the working and auxiliary electrodes, recording the redox reactions occurring within the corresponding potential range to obtain voltage-current curves. This allows for the determination of information such as the electrolyte's boundary potential and the reversibility of electrode reactions. This experiment was conducted on a VMP3 electrochemical workstation. Stainless steel sheets were labeled SS, and a battery with an SS|membrane|Li structure was assembled. The LSV testing conditions were: a scan rate of 5 mV / s. -1 The starting point is -1V, the ending potential is 5V / 6V, and the data recording time interval is 0.0002s.
[0089] like Figure 6 As shown in Figure a, compared to the PEO / LiTFSI electrolyte prepared in Comparative Example 1, the CSPEs prepared in Example 1 have a wider electrochemical window at 60°C; the CSPEs do not undergo redox reactions within the range of 0-4.55V. However, the current begins to increase sharply after 4.55V, indicating that the polymer electrolyte is gradually oxidized. Therefore, the electrochemical window of the CSPEs is 4.55V (vs. Li). + / Li) can support the battery to operate over a wide voltage range.
[0090] The impedance spectra of the batteries assembled from the two electrolyte systems prepared in Comparative Example 1 and Example 1 are as follows: Figure 6 As shown in b, the battery impedance corresponding to CSPEs is 75Ω, lower than the 100Ω of PEO / LiTFSI electrolyte. This corresponds to the ionic conductivity test results below. Figure 6 As shown in c, adding 10% by mass of the single-ion polymer LiPEBI to the PEO / LiTFSI system yields the composite solid polymer electrolyte with the highest ionic conductivity. More importantly, the ionic conductivity of 10% CSPEs at room temperature and 60°C are 7.69 × 10⁻⁶. -6 S cm -1 and 4.16×10 -4 S cm -1All of these values are higher than the 2.83 × 10⁻⁶ of the PEO / LiTFSI electrolyte system. -6 S cm -1 and 2.40×10 -4 S cm -1 This may be due to the addition of polymer lithium salt, which to some extent inhibits PEO crystallization and enhances the segmental movement of the polymer chains. Furthermore, it also benefits from the ion transport channels constructed by the single-ion polymer LiPEBI.
[0091] like Figure 6 As shown in Figure df, the rate performance of batteries assembled with the two electrolyte systems was tested at 60℃. The results show that the batteries exhibit stable and reversible charge-discharge capability at current densities of 0.1–1C, and a discharge specific capacity of 156.9 mAh g⁻¹ at a rate of 0.4C. -1 This is significantly higher than the 98.5 mAh g of the PEO / LiTFSI electrolyte. -1 .
[0092] The long-term cycling performance of the electrolyte was tested at 60°C and a current density of 0.4C. The results are as follows: Figure 6 As shown in g, the battery assembled using the CSPEs system has an initial discharge specific capacity of 137.3 mAh g at a current density of 0.4C and 60°C. -1 After 100 charge-discharge cycles, it still has 128.8 mAh g. -1 The capacity decreased by only 6.2% of the initial capacity, and the coulombic efficiency remained at around 98%. However, the battery assembled with PEO / LiTFSI electrolyte had an initial discharge specific capacity of 106.3 mAh g⁻¹. -1 After 100 charge-discharge cycles, it only has 83.2 mAh g. -1 The capacity retention was 21.7% lower than the initial capacity. These tests demonstrate more stable electrochemical performance and capacity retention, which is beneficial for applications in high-energy-density lithium metal batteries. The rate and cycle performance of the electrolyte were evaluated using a LiFePO4|Li battery. The preparation process of the LiFePO4 cathode is as follows: a certain amount of active material (LiFePO4), acetylene black (AB) conductive additive, and PVDF binder in a mass ratio of 7:2:1 were weighed and dissolved in a calculated amount of N-methylpyrrolidone (NMP) to form a slurry. This slurry was then cast onto aluminum foil using a coating machine. Subsequently, the coated aluminum foil was dried in a forced-air oven at 60°C for 12 hours, then cut into 15nm discs for use as the cathode of the coin cell, and transferred to a vacuum oven at 80°C for overnight drying.
Claims
1. A method for preparing a composite solid polymer electrolyte (CSPE) membrane, characterized in that: Includes the following steps: Weigh out polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and single-ion polymer electrolyte (LiPEBI) according to the specified ratio, mix them, and dissolve them in deionized water; then heat the resulting mixed solution to 50–70°C. o Stir at constant temperature for 10-15 h; uniformly coat the solution obtained after stirring onto the substrate surface, dry, and finally remove it from the substrate to obtain the composite solid polymer electrolyte CSPEs membrane. The single-ion polymer electrolyte LiPEBI is prepared by the following method, including the following steps: Weigh an appropriate amount of bis(bissulfonylimide)benzenediacarboxylic acid precursor OX-BCSI and place it in a double-necked flask 1 equipped with a water separator. Then, add anhydrous lithium chloride according to the ratio, purify the mixture with cooling water, and then introduce pure argon gas into the double-necked flask 1 to protect the reaction. Next, weigh anhydrous N-methylpyrrolidone (NMP), pyridine (Py), and triphenyl phosphite (TPP) according to the ratio and add them sequentially to the double-necked flask 1. After stirring and dissolving at room temperature, continue to add 1,2-bis(2-aminoethoxy)ethane to the reaction system. Then, heat the system to 80-120°C. o C, react at a constant temperature for 20-30 h; after the reaction is completed, cool to room temperature, precipitate the yellow solid in the obtained reaction solution, filter, wash the obtained filter cake to obtain the yellow product; finally, dry the yellow product, lithiate it, filter it after complete lithiation, wash the obtained filter cake, dry it to obtain the target product single ion polymer electrolyte LiPEBI. The di(bis(sulfonylimide)benzenedicarboxylic acid precursor was prepared by the following method, with the following steps: (1) Weigh p-toluenesulfonyl and potassium hydroxide into a reaction flask according to the ratio, then add deionized water and stir until completely dissolved; adjust the temperature of the resulting solution to 75-85°C. o C. Weigh out 4,4'-oxobis(benzenesulfonyl chloride) according to the ratio and slowly add it to the reaction flask in batches; after the addition is complete, adjust the reaction temperature to 90-100°C. o The reaction is carried out at a constant temperature for 10-15 hours. After the reaction was completed, dilute hydrochloric acid solution was added to the product while it was still hot to adjust the pH of the product to 7; then the product was filtered, the filtrate was collected, and dilute hydrochloric acid solution was added to the filtrate to adjust the pH of the filtrate to 1, resulting in a milky white precipitate. The white precipitate was collected by centrifugation and recrystallized to obtain the di(bis(sulfonylimide)phenyldimethyl precursor OX-BMSI). (2) Synthesis of OX-BCSI Weigh the OX-BMSI and potassium hydroxide from step (1) according to the specified ratio, and add them sequentially to a double-necked flask 2 equipped with a water separator. Then add deionized water, and after complete dissolution, heat the system to 85-95°C. o C, introduce condensate; then at 85-95 o Potassium permanganate was slowly added to the double-necked flask 2 under C conditions. After the addition was complete, the mixture was stirred at a constant temperature for 10-15 h. After the reaction was completed, the mixture was cooled to room temperature, and the resulting product was filtered. Excess concentrated hydrochloric acid was added dropwise to the filtrate, and the mixture was allowed to stand. The mixture was then filtered again to obtain the crude product. Finally, the product was recrystallized and dried to obtain the di(bis(sulfonylimide)benzenediacarboxylic acid precursor OX-BCSI.
2. The method according to claim 1, characterized in that: The EO in PEO and the Li in LiTFSI + The molar ratio is 45:
1.
3. The method according to claim 1, characterized in that: The amount of the single-ion polymer electrolyte LiPEBI added is 10% of the total mass of PEO and LiTFSI.
4. The method according to claim 1, characterized in that: The molar ratio of the di(bis(sulfonylimide)benzenediacarboxylic acid) precursor to anhydrous lithium chloride is 1:
4.
5. The method according to claim 1, characterized in that: The molar ratio of the di(bis(sulfonylimide)benzenediacarboxylic acid) precursor to 1,2-bis(2-aminoethoxy)ethane is 1:
1.
6. The composite solid polymer electrolyte (CSPE) membrane prepared by the method according to any one of claims 1 to 5.
7. The application of the composite solid polymer electrolyte (CSPE) separator prepared by the method according to any one of claims 1 to 5 in lithium metal batteries.
8. A lithium metal battery, comprising a positive electrode, a negative electrode, a solid electrolyte membrane, and a shell, wherein the solid electrolyte membrane is a composite solid polymer electrolyte (CSPE) separator prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Composite polymer solid electrolyte and preparation method thereof
CN108448167A
Composite polymer solid electrolyte and preparation method thereof
CN111816917A